DEVELOPMENT OF SPATIAL AND MASS ON KERATON KASEPUHAN CIREBON - Deby Sinantya Purbodewi ; Rahadian P. Herwindo (Riset Arsitektur (RISA), 2019)
Abstract- Keraton Kasepuhan Cirebon is one of the oldest palace that built during the transition era of Hindu Buddhism and Islam. Therefore. Keraton Kasepuhan has many periods of cultural period, where each period of time has its own distinctive culture, especially from special activities and daily activities that can affect the needs that create a spatial pattern. In terms of architecture, the existence of cultural influences resulted in the development of spatial and mass patterns, so that Kasepuhan Palace has elements of the culture in the spatial pattern and mass. According to the results of previous research, the culture is: Hindu-Buddhist, Islam, and also Colonial.  Using linear analytical methods, the data were analyzed by discussing according to the history of spatial development from the influence of each culture. The data were analyzed based on the composition of the HinduBuddhist, Islamic, Chinese, and Colonial spatial layout with the spatial development in the history of the Kasepuhan Palace, which was divided into four ages of leadership namely Ketemenggungan, Kesunanan, Panembahan and Kasultanan, in the focus of large-scale contexts, sacred building contexts, residential buildings.  This study aims to tell the architectural pattern that form Keraton Kasepuhan. The benefits of the completion of this research are to add to the architectural treasury of spatial and mass principles by various cultures in Indonesia, and add insight into the principles of spatial and mass arrangement based on theory and culture.  The conclusion of this research is the development of spatial and mass on Keraton Kasepuhan is most influenced by local culture, Hindu and Javanese Islam, while the outside culture does not much influence especially on spatial and mass Keraton Kasepuhan. In this case also found that the spatial and mass of a building can survive in a long time, while the form elements in the building can whenever changed and can be adopted or inspired from any culture. Spatial and mass is very crucial, it is the key to the relationship of architecture with humans.  Key Words: Acculturation, Spatial and Mass, History, Keraton, Keraton Kasepuhan Cirebon